Tailored immunotherapy approach with Nivolumab in advanced transitional cell carcinoma - Grimm, Marc-Oliver; Schmitz-Dräger, Bernd Jürgen; Zimmermann, Uwe; Grün, Barbara; Baretton, Gustavo Bruno; Schmitz, Marc; Foller, Susan; Leucht, Katharina; Schostak, Martin; Zengerling, Friedemann H.; Schumacher, Ulrike; Loidl, Wolfgang; et al. (Journal of clinical oncology, 2022)
PURPOSE - - Several anti-programmed cell death (ligand)-1 (PD-[L]1) immune checkpoint inhibitors are approved in advanced/metastatic urothelial carcinoma (mUC). Recently, improved activity of an anti-PD-1/anticytotoxic T-cell lymphocyte-4 (CTLA-4) combination versus anti-PD-1 monotherapy has been reported. We report a response-based approach starting treatment with nivolumab monotherapy with nivolumab/ipilimumab as immunotherapeutic boost. - - METHODS - - After four doses of nivolumab induction, responders continued with nivolumab maintenance therapy. Patients with stable/progressive disease received nivolumab 3 mg/kg plus ipilimumab 1 mg/kg once every 3 weeks for 2 doses followed by nivolumab 1 mg/kg plus ipilimumab 3 mg/kg once every 3 weeks for 2 doses, if not responding to the initial boost. Responders to boosts continued with nivolumab maintenance. Between July 2017 and April 2019, 86 patients were enrolled. The median follow-up is 7.7 months. The primary end point is objective response rate (ORR) per RECIST1.1. Secondary end points include efficacy of nivolumab induction, remission rate with nivolumab/ipilimumab boosts, overall survival, and safety. - - RESULTS - - Of all patients, 42, 39, and five were first- (1L), second- (2L), and third-line (3L), respectively. The median age was 68 years. The ORR with nivolumab monotherapy (assessed at week 8) was 29% in 1L and 23% in 2/3L, respectively. Forty-one patients received early (week 8) and 11 received later nivolumab/ipilimumab boosts. ORRs with nivolumab with or without nivolumab/ipilimumab (best overall response) were 45% and 27% in 1L and 2/3L, respectively. In 1L, 7 of 17 patients receiving boosts at week 8 improved, compared with 2 of 24 in 2/3L. - - CONCLUSION - - The tailored approach of TITAN-TCC shows meaningful clinical activity supporting dual checkpoint inhibition in 1L mUC. However, starting therapy with nivolumab exclusively appears inadequate given the aggressive nature of mUC. In 2/3L, nivolumab/ipilimumab boosts with escalating ipilimumab dose did not improve efficacy outcomes versus nivolumab monotherapy. An independent 2L cohort of TITAN-TCC receiving nivolumab 1 mg/kg plus ipilimumab 3 mg/kg once every 3 weeks for 4 doses is ongoing.